2008
DOI: 10.1021/ie071467m
|View full text |Cite
|
Sign up to set email alerts
|

Description of Thermodynamic Behavior of the Systems Formed by Alkyl Ethanoates with 1-Chloroalkanes Using the COSMO-RS Methodology Contributing with New Experimental Information

Abstract: For this work, V m E and H m E have been measured at a temperature of 298.15 K and at atmospheric pressure for a set of binary mixtures composed of seven alkyl ethanoates (from methyl to octyl, except heptyl) and six 1-chloroalkanes (C 4 to C 9 ). Of the 42 binary mixtures, measurements have only been made for systems for which the excess quantities have not been published previously. Except for the octyl ethanoate +1-chlorobutane system, with V m E < 0, and hexyl ethanoate+1-chlorobutane, with V m E ≈ 0, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…Previous studies have demonstrated a difference between the values of H E m in the mixtures of mono-and dihalides with a second compound of the same class, as verified in the (ester + monochloroalkane) [13], which also occurred for derivatives of bromide that we will demonstrate in a future work on monobromides. The differences in H E m , with higher values in mixtures with the monohalides, Cl or Br, are associated with increased acidity of the hydrogens after adding a Cl or Br atom to the compound.…”
Section: Resultsmentioning
confidence: 65%
“…Previous studies have demonstrated a difference between the values of H E m in the mixtures of mono-and dihalides with a second compound of the same class, as verified in the (ester + monochloroalkane) [13], which also occurred for derivatives of bromide that we will demonstrate in a future work on monobromides. The differences in H E m , with higher values in mixtures with the monohalides, Cl or Br, are associated with increased acidity of the hydrogens after adding a Cl or Br atom to the compound.…”
Section: Resultsmentioning
confidence: 65%
“…Adequate estimations are observed for the 1,2-dichloroethane, but the predictions tend to diverge as the length of the dichloroalkane chain increases. In order to obtain a better prediction of the H E m for the mixtures selected, as described previously for halogenated compounds [8,20], the COSMO-RS parameters must be fine-tuned. As a result, the original values for the van der Waals interactions s(Cl, Cl) = À39.60 kJ/mol/nm 2 and s(Cl, H) = À26.06 kJ/mol/nm 2 , presented in the literature cited previously, have been replaced, respectively, by À45.54 and À36.48 kJ/mol/nm 2 .…”
Section: Application Of the Cosmo-rs To Pure Componentsmentioning
confidence: 99%
“…In a first step, as indicated in a previous paper [8], the molecular geometries of the components of the mixtures were optimized using the Guassian03 quantum-chemistry software [17] to the calculus level B3LYP/6-311++G ** . This is later used to generate files which contain the information required to apply the continuous solvation COSMO model to the BVP86/TZVP/DGA1 level.…”
Section: Application Of the Cosmo-rs Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenomena related to the adsorption of organic solutes on AC have been shown to depend on the structural and physico-chemical properties of both adsorbate and adsorbent, which determine the contribution of polar, Van de Waals and hydrogen bonding interactions to the adsorption potential [1]. COSMO-RS has shown general suitability for calculating thermodynamic properties of fluid mixtures from electronic information of individual molecules [13], such as Gibbs free energies and equilibrium constants of reaction [14], L-L equilibrium data as solubility [15] and partition coefficients [16], excess enthalpy [17] and pK a values [18]. In addition, COSMO-RS has been successfully applied to predict adsorption equilibrium data from aqueous solutions [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%